Археологічні дослідження оборонних укріплень літописного Володимира в 2018 р. - Панишко, С.Д.; Петраускас, А.В.; Чорний, І.О. (Археологія і давня історія України, 2022)
У статті дані результати археологічного дослідження внутрішньої будови валу городища
«Вали» у центрі м. Володимир. Встановлено, що
вал насипали, вірогідно, у XV ст. Таке датування
виключає можливість пов’язати городище з дитинцем літописного Володимира та уможливлює
його співвіднесення зі старостинським дерев’яно-земляним замком. For the first time in the history of archeological
research in Volodymyr the cross-section of the ramparts
of «Valy» hill-fort were made. According to external
morphological features the hill-fort belongs to
the «Volyn type», and most researchers consider it to
be remains of the citadel of annalistic city. There is no
direct evidence of the latter but the available written
sources directly indicate the location of the brick castle
of Casimir the Great in the 14th century and the later
wooden-earthen headman’s castle. Just the main task
of the work was to ascertain the conformity of the ramparts
to these objects.
The internal structure of the rampart was explored
by laying a stepped trench measuring 2 × 11 m at the
end of the rampart at the place of its gap (entrance to
the territory of hill-fort). The cross-section made it possible
to record the stratigraphic column of layers and
backfills for more than 6 m long and to ascertain the
general picture of the rampart construction.
It was learned that the embankment of the rampart
was carried out above the level of the cultural layer
which occured on a yellow homogeneous loess-like
loam (possibly the virgin soil). The generalization of
the layers traced above for 5.96 m allows us to identify
three of their main groups which probably reflect the
sequence of erecting of the rampart at this area.
The first large-scale backfill, which formed the basis
of the embankment, was traced in the square 5. It consisted
mainly of yellow loess-like loam with inclusions
of limestone fragments.
The middle part of the embankment was explored
in squares 2—4, where the complex stratigraphic sequence
of various layers and strata have been traced,
which, in addition to loess-like yellow loam with limestone
fragments, included the larger backfills of dark
gray sand with inclusions of yellow loam and the same
soil with inclusions of debris.
Finally, the upper part of the embankment, explored
in the square 1, consisted of dark gray humused sand
with inclusions of clay and charcoal. Since this layer
contained a lot of pottery of the Late Middle Ages, it is
possible that this is a filling of the late medieval building
inserted into the embankment.
The research revealed material from different times,
dating from the Bronze Age to nowadays. The dating of
the embankment of rampart is indicated by the findings
of late medieval pottery in its middle part. They
confirm the written reports about the construction of a
wooden-earthen headman’s castle in the 15th century.
Some structural features of the rampart are in good
agreement with historical data. In particular, the first
backfill at the base of the embankment of yellow loesslike
loam had significant inclusions of fragments of
limestone, which may be the remains of the masonry
of the walls of Casimir the Great castle, dismantled in
1370.
Dating the construction of rampart to the 15th century
indicates that the explored hill-fort was not the citadel
of Old Volodymyr. On the other hand, it allows us
to re-date at least the part of hill-forts of «Volyn type»,
which are traditionally attributed to the 10th—11th centuries.